When vulnerabilities are exploited—The role of sextortion in the WASH sector in Bangladesh - Merkle, Ortrun; Allakulov, Umrbek; Gonzalez, Debora; Sánchez, Alfredo Hernández; Rabbi, Sifat E.; Hasan, Zobair (Frontiers in Water, 2023)
It has long been acknowledged that many aspects of Water, Sanitation, and Hygiene (WASH) are highly gendered and that women face an increased risk of violence when access to WASH services is not adequate. However, not enough studies explore where these incidents of violence occur or document the different forms of violence. This research paper will add to the newly emerging research on sextortion as a form of violence that women and girls encounter disproportionately in accessing WASH. This form of violence that takes place at the intersection of corruption and sexual violence has dire social, economic and health consequences, yet little is known as of what increases vulnerability to sextortion. Analysing original data from a standardized survey with adult women (n=1200), interviews (n=21) and focus group discussions (n=5), this paper examines the factors that make women vulnerable to sextortion in accessing WASH services. The study was conducted in 2 rural and 2 urban areas in Bangladesh between September and December 2021. The analysis shows that those women living in poverty, in water insecure households and in rural areas are especially vulnerable to experiencing sextortion. The research also shows that the vulnerability factors, while overlapping are not the same as those making women vulnerable to experiencing sexual and gender-based violence, highlighting the importance of studying sextortion separately. The findings contribute to an emerging evidence-base around sextortion, which remains an understudied phenomenon posing an obstacle to the achievement of safe access to water and sanitation for all.